SERVICE LEARNING: PENGUATAN PENDIDIKAN KARAKTER DAN BUDAYA LOKAL MELALUI EKSPLORASI ALAM DALAM MENCEGAH DAMPAK NEGATIF GADGET DI SEKOLAH DASAR - Khasanah, Uswatun; Rovika, Tika; Lestari, Rina Kasih; Anbiya, Bakti Fatwa (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The purpose of this Community Service activity was to strengthen the character of elementary school students in the digital era while fostering a sense of love and appreciation for local culture. The target participants were students of Sekolah Dasar Negeri (SDN) 04 Lerep, specifically grades 4 to 6, with a total of 68 students involved in the program. The activity implemented a service-learning method, which integrates direct learning experiences with community engagement. This approach combined educational activities with practical community-based initiatives to enhance students’ character development. Nature exploration was incorporated as a strategy to reduce students’ dependence on digital gadgets while simultaneously introducing and reinforcing local cultural values. Through interactive and experiential learning, students were encouraged to actively participate, reflect, and apply positive behaviors in their daily lives. The results of the program indicated improved understanding regarding responsible gadget use, character education, and greater awareness and appreciation of local cultural heritage among the students.